Comparative study of specific physical abilities to prove the efficacy of working with performance subgroups. - Nicolás Castellanos Gil; Roberto Rodríguez Valdés; Raúl López Fernández (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2005)
Background: Sport and Physical Education improve studying capacity. It is part of nowadays men, as a way of fighting inactivity caused by fast development. Objective: To suggest a strategy of subgroups-work to develop some physical capacities. Methods: This work is based on some physical aptitude tests and on Ruffier test; comparing them to proof that work through proficiency subgroup is effective to improve skills. We used SPSS for data processing and determined maximum and minimal values comparing measures for independent samples which determined changes. This allowed an objective assessment of our work useful for improved class planning as for a future assessment of the program. Results: This work is a scientifically supported document for possible modifications of Physical Education curriculums in Medicine Studies.